Las protestas del trabajo en la primavera de 1936 - Francisco Sánchez Pérez (Mélanges de la Casa de Velázquez, 2011)
This article seeks to throw some light on the relationship between the triumph of the left coalition in February 1936, swiftly dubbed the Popular Front, and the virulent outbreak of labour and urban protests and conflicts that followed this triumph. After February 1936 the workers expected to see political change and a restoration of labour relations as they were before October 1934. In this context the paper examines this new wave of strikes: in the countryside the decline of agrarian strikes and the multiplication of land invasions and occupations; in industry, inter-union collaboration and the persistence of frictions among them; the impact of the crisis and unemployment on some of the most radicalised sectors (construction); the uneven distribution of strife and the preponderant role of Madrid; the role of sectors with no union tradition; and the role of political and sit-down strikes.